2018
DOI: 10.1002/ar.23777
|View full text |Cite
|
Sign up to set email alerts
|

HMGA1 Overexpression is Associated With the Malignant Status and Progression of Breast Cancer

Abstract: Breast cancer is the most common malignant tumor among women, and the incidence and mortality of breast cancer has rapidly increased in recent years. Studies have indicated that high mobility group A1 (HMGA1), an important member of the HMGA family, plays a role in the pathogenesis and progression of malignant tumors, including breast cancer. This study aims to evaluate the effect of HMGA1 in breast cancer. Interestingly, we found that HMGA1 expression was significantly higher in breast cancer tissues than in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 28 publications
2
9
0
Order By: Relevance
“…Our findings showed slightly higher HMGA1 expression in initial biopsies taken from non-responders, as well as an inverse expression pattern in post-induction biopsies (Figure 4B), but these results and, similarly, the results of the survival analysis (Figures 5C,D) were not statistically significant. Nevertheless, such trends in expression—although non-significant—are in accordance with recent knowledge on the importance of HMGA1 as a “master regulator” in tumorigenesis and its association with tumor aggressiveness (32, 34, 38).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Our findings showed slightly higher HMGA1 expression in initial biopsies taken from non-responders, as well as an inverse expression pattern in post-induction biopsies (Figure 4B), but these results and, similarly, the results of the survival analysis (Figures 5C,D) were not statistically significant. Nevertheless, such trends in expression—although non-significant—are in accordance with recent knowledge on the importance of HMGA1 as a “master regulator” in tumorigenesis and its association with tumor aggressiveness (32, 34, 38).…”
Section: Discussionsupporting
confidence: 86%
“…Treatment with retinoids can change the expression of HMGA1, and these changes are closely related to MYCN status (30, 31). Although there are no data on the possible relationship between HMGA1 expression and clinical outcome in patients suffering from NBL, published studies on other cancer types suggest that HMGA1 overexpression is associated with aggressive tumor behavior and poor prognosis: such findings were reported for breast carcinoma (3234), pancreatic adenocarcinoma (35), esophageal squamous cell carcinoma (36), non-small cell lung cancer (37), and uveal melanomas (38). In contrast, such results were not confirmed by other research groups for gastric cancer (39) and non-small cell lung cancer (40).…”
Section: Discussionmentioning
confidence: 99%
“… 41–43 Amounting studies proved that the suppression of oncogenic HMGA1 significantly inhibited some cancer cell proliferation and migration, providing a novel clue to probe into anti-cancer approaches. 21 , 29 , 32 , 44 , 45 Furthermore, HMGA1 is up-regulated in a significant proportion of HCC, and its overexpression is associated with a poor prognosis. A research in vitro models ulteriorly elucidated that HMGA1 overexpression may act a pivotal role in cell viability and migration and promote anchorage-independent growth to induce transformation in liver cancer cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…High expression of HMGA1 has been reported to play an important role in embryonic development [ 22 , 23 ]. Recent studies have revealed that HMGA1 is associated with various types of cancers including breast [ 24 , 25 ], lung [ 26 , 27 ], and colorectal [ 28 , 29 ] cancer types. Although several studies have shown that HMGA1 plays an important role in the development of HCC [ 30 , 31 ], only one study has reported that the recurrence rate of HCC correlated with high HMGA1 mRNA expression and that it could be used as a prognostic marker for HCC [ 32 ].…”
Section: Discussionmentioning
confidence: 99%